Teenagers' Purchasing Decisions: Shopping Lifestyle and Brand Ambassadors' Influence: Pengaruh Gaya Belanja dan Duta Merek terhadap Keputusan Pembelian Produk Perawatan Tubuh Pria: Studi Kuantitatif pada Remaja - Huda, Ahmad Fatkul; Purwanto, Nuri (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aimed to investigate the impact of shopping lifestyle and brand ambassadors on the purchasing decisions of MS GLOW FOR MEN body care products among teenagers in Jombang Regency. The sample consisted of 100 individuals selected using simple random sampling. Data was collected through questionnaires and literature review. SPSS analysis revealed a significant positive effect of shopping lifestyle and brand ambassador variables on the decision to purchase MS GLOW FOR MEN products. These findings contribute to understanding consumer behavior in the skincare market, emphasizing the importance of marketing strategies that incorporate brand ambassadors and cater to diverse shopping lifestyles for successful product sales and brand loyalty. Highlights: Significance of Brand Ambassadors: Explore the impact of brand ambassadors on consumer purchasing decisions for men's body care products. Influence of Shopping Lifestyle: Investigate how shopping lifestyle affects the choice of MS GLOW FOR MEN products among teenagers. Quantitative Analysis: Utilize SPSS to analyze data and establish the relationship between key variables in the skincare market. Keywords: Shopping Lifestyle, Brand Ambassadors, Men's Body Care Products, Consumer Purchasing Decisions